Maternal diabetes and neonatal outcome - Valentin Varlas; Maria Ciocarlan; Roxana Elena Bohiltea; Vlad Dima (Romanian Journal of Pediatrics, 2021)
Diabetes during pregnancy is more and more frequent worldwide because of the rising incidence of its known risk factors, such as high body mass index, sedentary lifestyle, and hypercaloric diets. It can be either a preexisting condition, or it can be first diagnosed during pregnancy, usually between the 24th and the 28th week of gestation, when it receives the name of gestational diabetes mellitus. Both preexisting diabetes mellitus and gestational diabetes mellitus may have severe maternal and newborn consequences, especially if there is insufficient control of the maternal glycemic levels and progression of diabetes complications, such as microvascular disease and nephropathy. Infants of diabetic mothers may experience excessive birth weight or, on the contrary, low birth weight, trauma at birth, cardiomyopathy, respiratory distress syndrome, hypoglycemia, hypocalcemia, jaundice, or polycythemia. This study’s aim is to gather and synthesize available information about maternal diabetes and its impact on fetal development and newborn outcome.